DETERMINATION OF PHYSICOCHEMICAL PROPERTIES, ANTIOXIDANT CONSTITUENTS BY HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY FINGERPRINTING, AND ANTIOXIDANT ACTIVITY OF CUCURBITA MAXIMA SEEDS - Pal, Pinki; Singh, Shiv Bhadra; Singh, Aaditya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study is designed to evaluate preliminary phytochemical constituents, physiochemical properties evaluation, free radical scavenging activity, and high-performance thin-layer chromatography (HPTLC) fingerprinting analysis of Cucurbita maxima seed oil. Methods: Total phenol content, total flavonoid content, total tannin content, 1, 1-diphenyl, 2-picryl-hydrazyl (DPPH) radical scavenging method, and HPTLC fingerprinting analysis for compounds responsible for antioxidant activity were used. Result: Phytochemical screening shows the presence of constituents such as alkaloids, glycosides, carbohydrates, fixed oil and fats, phytosterols, saponin, phenolic compounds, tannins, proteins, amino acids, gums, and mucilage. Physicochemical studies show that the oil contains an acid value, saponification value, iodine value of 9.53 mg KOH/g, 183 mg KOH/g, and 116.51 mg I2/100 g, respectively. Total phenol content was 3.9498Â±3.2 mg gallic acid equivalent/g, total flavonoid content was 56.115Â±4.6 mg rutin equivalent/g, and total tannin content was 19.4Â±0.40 mg tannic acid equivalent/g. The radical scavenging activity by DPPH Model shows that the methanolic extract has maximum antioxidant activity with IC50 value of 238.31. HPTLC fingerprinting also proofs the presence of phenol and flavonoid compounds in the seed oil. Conclusion: The results in the paper show that the C. maxima seed oil is an natural antioxidant and can be used for the treatment of various disorders.